I've worked the slope all the way down to $\sum [x_i(y_i - \bar{y})] = \hat\beta_1 \sum[x_i(x_i - \bar{x})]$

But I can not figure out how to show the steps for:

$\sum[x_i(y_i - \bar{y})] = \sum(x_i - \bar{x})(y_i - \bar{y})$


$\hat \beta_1 \sum[x_i(x_i - \bar{x})] = \hat \beta_1 \sum(x_i - \bar{x})^2$

  • $\begingroup$ Probably $x_i$ are centralised ( Original variable is subtracted by its mean value). If that is the case $\bar{x} =0$. $\endgroup$
    – vinux
    Mar 27 '12 at 3:51
  • 1
    $\begingroup$ @vinux, usually if some term is in the equation it is assumed that it is not zero. $\endgroup$
    – mpiktas
    Mar 27 '12 at 7:25

Add and subtract and then look whether the unwanted term disappears:

$$\sum[x_i(y_i-\bar y)]=\sum[(x_i-\bar x+\bar x)(y_i-\bar y)]=\sum[(x_i-\bar x)(y_i-\bar y)]+\sum [\bar x(y_i-\bar y)].$$


$$\sum [\bar x(y_i-\bar y)]=\bar x\sum [y_i-\bar y]=\bar x\left[\sum y_i-n\bar y\right]=0,$$

where $n$ is the number of the terms in the sum. Apply the same trick for the second equation.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.